Completeness versus Incompleteness: Binary Codification of the Pop Song "Que Marianne était jolie". Issue 1 (2nd January 2018) - Wagner, Anne
Abstract: "Que Marianne était jolie, " a well-known French popular song of the 1970s, is a space of possibilities, a realm of "cross-cultural events, " where interpretation is deeply rooted in French history and societal evolution. The main complexity in deciphering the coded meaning of its lyrics is to analyze the source space and time (first element of the binary code: the revolutionary codification), and to view how the same symbols were "appropriated, translated, rehistorized, and read anew" in the song (second element of the binary code: the republican codification). The use of visual art as an interpretative tool here aims at better decoding and reading the contexts, the concepts and the shifts in meanings, and ensuring we can comprehend the main character, plot, and settings implicit in this pop song.